Highly sensitive and specific responses of shrimp gill cells to high pH stress based on single cell RNA-seq analysis - Ge, Qianqian; Wang, Jiajia; Li, Jitao; Li, Jian (Frontiers in Cell and Developmental Biology, 2022)
High pH is one of the main stressors affecting the shrimp survival, growth, and physiology in aquaculture ponds, but the cellular and molecular mechanism responsible for high pH stress has not been elucidated in shrimp. In this study, the shrimp acid-base disturbance and gill cell alterations were significantly observed and then single cell RNA-sequencing (scRNA-seq) was performed to study the sensitive and specific responses of gill cells to high pH stress. Three main gill cell types, including pillar cells, hemocytes and septal cells were identified. By comparative scRNA-seq analysis between control and pH group, the pillar cell was regarded as the target cell type in response to high pH stress with the down-regulation of ammonia excretion and H+ transport related genes and up-regulation of immune related genes. Notedly, high pH resulted in the emergence of a new immune cell subcluster in pillar cells, with immune activation and stress defense states. Pseudotime analysis also showed that the pillar cells could transform into the functionally inhibited ion cell subclusters and functionally activated immune cell subclusters after high pH stress. Further, the regulatory network of pillar cell population was predicted by WGCNA and two transcription factors were identified. In conclusion, these results provide key insights into the shrimp gill cell-type-specific mechanisms underlying high pH stress response at a single-cell resolution.